Antimony diiminopyridine complexes. Issue 34 (18th August 2021) - Tidwell, John R.; Dutton, Jason L.; Martin, Caleb D.
Abstract : The stoichiometric reactions of antimony trichloride, trimethylsilyl trifluoromethanesulfonate, and diiminopyridine ligands lead to the formation of the first antimony diiminopyridine complexes. Abstract : The stoichiometric reactions of antimony trichloride, trimethylsilyl trifluoromethanesulfonate, and diiminopyridine ligands lead to the formation of N, N ′, N ′′-chelated SbCl2 cationic complexes. Methyl and phenyl substituents on the imine carbons of the ligand yielded structures with a lone pair on antimony and the hydrogen substituted variant was notably different as it forms a Menshutkin complex with meta -xylene in the solid-state.